Between the body and the ancestors: expressions of religious thought in the clothing of Zulu-speaking women in the Nongoma region of KwaZulu-Natal, South Africa - Boram-Hays, Carol (Southern African Humanities, 2018)
In the religious and philosophical thought of Zulu-speaking people the human body serves as a vehicle for spiritual forces. The body must be open to encounters with spiritual forces, while simultaneously protected from physical and spiritual threats. This state is especially true for women, who serve as conduits for the rebirth of ancestors. Clothing can be used to mediate encounters between the physical and spiritual worlds. Rather than the historical and political, this study examines the religious aspects of dress of women of the late twentieth century in the Nongoma region, South Africa. It develops a complex understanding of how women, as creators and wearers, use dress to navigate experiences unique to their gender.